GE_GERICHTE C/4108/2010 vom 28. Juni 2013 - GE Cour de justice (2013)
ACTION EN PATERNITÉ; PREUVE; DÉCISION DE RENVOI; TRIBUNAL FÉDÉRAL; FRAIS DE LA PROCÉDURE; DÉPENS | CC.252.2; CC.262.1; CC.262.3; CC.263.1.2; LTF.107.2